Administrative and political system and economy of the Kingdom of Kanesh - Robert Ghazaryan (Banber Arevelagitut'yan Instituti)
The state of Kanesh was one of the state formations established in Asia Minor during the Bronze Age. It played a significant role in the process of formation and establishment of the Hittite state (mid-XVII century BC - early XII century BC). The city was the second center of the Hittite state after Kussara, and its territory served as a base for the further expansion of the Hittite state. It is important to emphasize that the city was also the capital and the center of the international trade network (in more than forty cities) organized by Assyrians. The state structure of Kanesh, its system of government also had an influence on the Hittite state system. All these lead us to study and explore the history of that city-state, to have an understanding of its state order, economy, and socio-economic relations.